1998
DOI: 10.1161/01.res.82.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Action of Tropoelastin and Synthetic Elastin Sequences on Vascular Tone and on Free Ca 2+ Level in Human Vascular Endothelial Cells

Abstract: The elastic properties of extensible tissues such as arteries and skin are mainly due to the presence of elastic fibers whose major component is the extracellular matrix protein elastin. Pathophysiological degradation of this protein leads to the generation of elastin peptides that have been identified in the circulation in the ng/mL to microg/mL range. Similar concentrations of an elastin peptide preparation (kappa-elastin) were previously demonstrated to induce, among other biological actions, a dose- and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 39 publications
(42 reference statements)
2
54
0
Order By: Relevance
“…This effect diminished in response to treatment with laminin and lactose, which implicated the surface receptor, elastin binding protein which in turn leads to increased intracellular calcium [6]. Here, we show tropoelastin has a potent effect in inducing nitric oxide production by endothelial cells and that their exposure to tropoelastin leads to the activation of eNOS.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This effect diminished in response to treatment with laminin and lactose, which implicated the surface receptor, elastin binding protein which in turn leads to increased intracellular calcium [6]. Here, we show tropoelastin has a potent effect in inducing nitric oxide production by endothelial cells and that their exposure to tropoelastin leads to the activation of eNOS.…”
Section: Discussionmentioning
confidence: 63%
“…While cell signaling is directed by tropoelastin through cell-surface interactions [2], specific integrin binding sites have been recently identified in tropoelastin where they drive the attachment and proliferation of fibroblasts, endothelial and endothelial progenitor cells [3][4][5]. Also contained within the tropoelastin sequence are short repeating hydrophobic signaling motifs that are recognized by the elastin binding protein (EBP) and promote cellular chemotaxis and vasorelaxation [6].…”
mentioning
confidence: 99%
“…Indeed, other extracellular matrix-derived proteins, such as endostatin and elastin peptides, have been shown to be potent vasoactive compounds that not only affect vascularization but also vascular tone regulation. 12,13 In the present study we have, therefore, investigated the impact of the LNP CDPGYIGSR on vascular tone and found that it induced vasoconstriction in murine and human systemic but not pulmonary arteries. This effect was mediated by depolarization of vascular smooth muscle cells via nonselective cation channels (NSCCs) and transmembrane Ca 2ϩ influx through L-type Ca 2ϩ channels and could be also found in vivo.…”
mentioning
confidence: 86%
“…Synthetic peptides based on key elastin sequences present elastin-like properties including self-assembly, cross-linking and cell interactions (Long, King et al 1989;Faury, Garnier et al 1998;Bellingham, Woodhouse et al 2001;Karnik, Brooke et al 2003;Karnik, Wythe et al 2003). Coating of materials with elastin peptides can improve biocompatibility by providing protein sequences required for cell binding (reviewed by (Almine, Bax et al 2010)).…”
Section: Synthetic Elastin-based Peptidesmentioning
confidence: 99%